Impact of lung ultrasound-guided therapeutic approach on haemodialysis treatment in patients with ischemic heart failure - Nejra Prohic; Belma Paralija; Halima Resic; Edin Begic (Medicinski glasnik, 2025)
Aim: Lung ultrasound (LUS) can be used for an assessment of volume overload in patients with end-stage kidney disease (ESKD) and those undergoing dialysis. The aim of this study was to analyse whether the initial use of LUS in evaluating volume status could benefit patients by optimizing haemodialysis treatment and improving their clinical status. Methods: The study included 50 haemodialysis patients in stage V of ESKD with the diagnosis of ischaemic heart failure with reduced (HFrEF) or midrange ejection fraction (HFmrEF). The assessment of volume status was verified solely by LUS (along with the analysis of B lines as measures of volume status). The specified laboratory parameters were performed initially, after three, and after six months. Results: The number of B-lines on LUS were decreased during the six-month follow-up compared to baseline, indicating a reduction in volume overload due to the LUS-guided protocol. Statistically significant differences were observed in the average creatinine (p=0.001) and parathormone (PTH) (p=0.003) levels over the six-month monitoring period. Significant differences were also noted in triglyceride (p=0.000) and potassium (p=0.02) levels. No significant differences were found in the values of other monitored parameters. Conclusion: In haemodialysis patients diagnosed with heart failure, LUS can aid the achievement of a more efficient volume reduction by decreasing B-lines, which are indicative of congestion. Our study also demonstrated beneficial effects of LUS on potassium and parathormone levels.
Keywords: kidney failure; prognosis; ultrasound